Charting a killer course to the solid tumor: strategies to recruit and activate NK cells in the tumor microenvironment - Portillo, Ana L.; Monteiro, Jonathan K.; Rojas, Eduardo A.; Ritchie, Tyrah M.; Gillgrass, Amy; Ashkar, Ali A. (Frontiers in Immunology, 2023)
The ability to expand and activate natural Killer (NK) cells ex vivo has dramatically changed the landscape in the development of novel adoptive cell therapies for treating cancer over the last decade. NK cells have become a key player for cancer immunotherapy due to their innate ability to kill malignant cells while not harming healthy cells, allowing their potential use as an “off-the-shelf” product. Furthermore, recent advancements in NK cell genetic engineering methods have enabled the efficient generation of chimeric antigen receptor (CAR)-expressing NK cells that can exert both CAR-dependent and antigen-independent killing. Clinically, CAR-NK cells have shown promising efficacy and safety for treating CD19-expressing hematologic malignancies. While the number of pre-clinical studies using CAR-NK cells continues to expand, it is evident that solid tumors pose a unique challenge to NK cell-based adoptive cell therapies. Major barriers for efficacy include low NK cell trafficking and infiltration into solid tumor sites, low persistence, and immunosuppression by the harsh solid tumor microenvironment (TME). In this review we discuss the barriers posed by the solid tumor that prevent immune cell trafficking and NK cell effector functions. We then discuss promising strategies to enhance NK cell infiltration into solid tumor sites and activation within the TME. This includes NK cell-intrinsic and -extrinsic mechanisms such as NK cell engineering to resist TME-mediated inhibition and use of tumor-targeted agents such as oncolytic viruses expressing chemoattracting and activating payloads. We then discuss opportunities and challenges for combination therapies to extend NK cell therapies for treatment of solid tumors.